Co-infections as Modulators of Disease Outcome: Minor Players or Major Players? - Devi, Priti; Khan, Azka; Chattopadhyay, Partha; Mehta, Priyanka; Sahni, Shweta; Sharma, Sachin; Pandey, Rajesh (Frontiers in Microbiology, 2021)
Human host and pathogen interaction is dynamic in nature and often modulated by co-pathogens with a functional role in delineating the physiological outcome of infection. Co-infection may present either as a pre-existing pathogen which is accentuated by the introduction of a new pathogen or may appear in the form of new infection acquired secondarily due to a compromised immune system. Using diverse examples of co-infecting pathogens such as Human Immunodeficiency Virus (HIV), Mycobacterium tuberculosis (MTb) and Hepatitis C Virus (HCV), we have highlighted the role of co-infections in modulating disease severity and clinical outcome. This interaction happens at multiple hierarchies, which are inclusive of stress and immunological responses and together modulate the disease severity. Already published literature provides much evidence in favour of the occurrence of co-infections during SARS-CoV-2 infection, which eventually impacts the COVID-19 outcome. The availability of biological models like 3D organoids, mice, cell lines and mathematical models provide us with an opportunity to understand the role and mechanism of specific co-infections. Exploration of multi-omics-based interactions across co-infecting pathogens may provide deeper insights into their role in disease modulation.